A method of measuring cochlear potentials evoked by two-tone excitation - Michalski, Wojciech; Dziewiszek, W.; Bochnia, M. (Archives of Acoustics, 2006)
This paper presents a new method of measuring cochlear microphonics (CM) evoked by a two-tone acoustic wave. The method is based on phase sensitive detection whereby it is possible to precisely measure not only excitation frequency CM signals but also combination signals. The method can be used in experiments conducted on animals. Exemplary experimental results are given.